Approved revenue recurrent and capital estimates, 1991 - Nigeria (Lagos : Printing Division, 1991)
This book is the 1991 fiscal year of the government of the federal republic of Nigeria.
osa 02/04/19
Loans
Keywords: Revenue; Budget; Budget; Expenditures, Public; Revenue; Public Finance; National budget; Nigeria